LIKUIDITAS KOPERASI PKK BUNGA ROSELA DI MUARA LAWA KABUPATEN KUTAI BARAT - Titin Ruliana, Desirita Vidiantuti, Elfreda Aplonia Lau. (EKONOMIA, 2016)
PKK Bunga Rosella Cooperation has capital from members' savings, the ministry grants and capital of the Government of Kutai Barat. The capital will be used as funds lent to the cooperative members. Voluntary savings can be withdrawn at any time so that the cooperative naturally have funds in anticipation of the withdrawal of these deposits.Formulation of the problem whether the PKK Bunga Rosella Cooperation has the ability to restore the voluntary savings of its members based on the cash ratio. This study aims to determine the liquidity ratio which is owned by the PKK Bunga Rosella CooperationÂ  and focused on the financial condition based on the balance in 2010, 2011, 2012 and 2013.Use basic theory of management accounting. Management accounting is used as a basis for taking a decision, using the tools of financial ratio analysis liquidity ratios particularly with the cash ratio method. By using the liquidity ratio analysis can be known ability of cooperatives where members want to attract voluntary savings. The reasearch hypothesis is PKK Bunga Rosella Cooperation has the ability to restore the voluntary savings of its members based on the cash ratio.Based on the analysis and discussion of the conclusions of this study as follows: The ratio of cash in 2010 amounted to 579.08%, in 2011 amounted to 266.72%, in 2012 amounted to 187.07% and in 2013 amounted to 147.74%. When compared with a hypothesis test indicate that the PKK Bunga Rosella Cooperation has the ability to restore the voluntary savings of its members based on the cash ratio, so the hypothesis can be accepted